HUBUNGAN PENGETAHUAN TENTANG MENARCHE DENGAN SIKAP MENGHADAPI MENARCHE PADA REMAJA PUTRI KELAS VII DI SMP SWASTA HANGTUAH STABAT TAHUN 2018 - Ria Julita Sari (Excellent Midwifery Journal, 2019)
Knowledge is the most important thing that must be owned by a teenager in the face of a change that is happening to him when menarche, a good knowledge of it will cause a great attitude while teenagers face menarche. The purpose of this research is to know the relation of knowledge of menarche with attitude faced menarche at young women in junior high Private Hangtuah Stabat Year 2018. This type of research is correlative with the design of Cross Sectional that aims to see the relationship between knowledge and attitudes of young women facing menarche using primary data or questionnaire. This research uses total population sebayak 30 respondents who examined entirely. The results obtained from this research that has a good knowledge of the 24 people (80%) have a positive attitude and 22 people (73.3%). Based on calculations by using analysis test significant values obtained Squre Chi 0.68. Because 0.68 > 0.05 then H0 is accepted and Ha was rejected. This means that it can be concluded that there is no relationship between knowledge with attitude of young women facing menarche. Expected to further researchers to be able to continue this research with a number of samples, design research and different places in order to strengthen the research and theory. Keywords        : Knowledge, Attitude